Enhanced biodegradation of used engine oil in soil amended with organic wastes - Abioye, P.O.; Abdul Raman, Abdul Aziz; Agamuthu, P. (2010)
Three organic wastes (banana skin (BS), brewery spent grain (BSG), and spent mushroom compost (SMC)) were used for bioremediation of soil spiked with used engine oil to determine the potential of these organic wastes in enhancing biodegradation of used oil in soil. The rates of biodegradation of the oil were studied for a period of 84 days under laboratory conditions. Hydrocarbon-utilizing bacterial counts were high in all the organic waste-amended soil ranging between 10.2 x 10(6) and 80.5 x 10(6) CFU/g compared to unamended control soil throughout the 84 days of study. Oil-contaminated soil amended with BSG showed the highest reduction in total petroleum hydrocarbon with net loss of 26.76 in 84 days compared to other treatments. First-order kinetic model revealed that BSG was the best of the three organic wastes used with biodegradation rate constant of 0.3163 day(-1) and half-life of 2.19 days. The results obtained demonstrated the potential of organic wastes for oil bioremediation in the order BSG > BS > SMC.